Effects of dietary arginine supplementation on growth performance, antioxidant capacity, intestinal digestive enzyme activity, muscle transcriptome, and gut health of Siniperca chuatsi - Ding, Liyun; Chen, Jiacheng; He, Fenglan; Chen, Qingtang; Li, Yiyi; Chen, Wenjing (Frontiers in Marine Science, 2024)
Our study investigated the effects of dietary arginine supplementation on the growth performance, antioxidant capacity, intestinal digestive enzyme activity, muscle transcriptome, and gut health of Chinese perch (Siniperca chuatsi). Four isonitrogenous and isolipidic diets (50% crude protein, 11% crude lipid) with graded levels (2.61%, 2.99%, 3.37%, and 3.82%) of arginine were formulated and processed. A total of 360 Chinese perch (approximately 45–46 g) were randomly divided into four groups with triplicates of 30 fish per cage in each group. Our results revealed that although there was no significant improvement in the growth performance of Chinese perch, their antioxidant capacity and nutritional metabolism were significantly improved. Compared to the control group (without arginine supplementation, 2.61% group), feeding graded arginine levels could significantly (P < 0.05) decrease serum glucose and malondialdehyde (MDA) contents, as well as increase total superoxide dismutase (TSOD) activity. Fish fed a 3.37% arginine diet had the highest TSOD activity in the serum and liver. The intestinal morphological structure was clearer and more uniform in the 2.99% and 3.37% arginine groups. Fish fed with 3.82% arginine had significantly decreased (P < 0.05) muscle valine, glutamate, tyrosine, and total non-essential amino acid contents, with decreased (P < 0.05) intestinal amylase activity. Transcriptome analysis showed that graded arginine levels significantly (P < 0.05) influenced muscle gene expression involved in the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways of energy metabolism (amino acid, glucose, fatty acid), signaling pathways (mTOR, PI3K-Akt, MAPK, foxO, and insulin pathway), etc. The microbial community structure did not change significantly. Mycoplasma showed the highest abundance in the control group, and Cetobacterium had the highest abundance in the dietary arginine supplementation groups. Network analysis showed that the network complexity of the control group was higher than those of arginine groups. Our finding would help advance the field of arginine nutrition and guide the development of future fish feeds. Based on antioxidant and intestinal health indicators, the optimal dietary arginine requirement for Chinese perch was 2.99%–3.37% of the dry diet (6.08%–6.79% of dietary protein).